2004
DOI: 10.1002/path.1529
|View full text |Cite
|
Sign up to set email alerts
|

Linkage of angiotensin I‐converting enzyme gene insertion/deletion polymorphism to the progression of human prostate cancer

Abstract: Angiotensin-converting enzyme (ACE) degrades vasodilator kinins and generates angiotensin II (Ang II). It has been reported that ACE is synthesized by the prostate and that the AT-1 receptor subtype is the predominant prostatic Ang II receptor. A polymorphism in the human ACE gene has been described and the highest levels of circulating and tissue ACE activity are found in carriers of the DD genotype. In the present study, ACE genotypes were determined in 170 patients with prostate cancer and their association… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
59
0
1

Year Published

2005
2005
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 76 publications
(62 citation statements)
references
References 56 publications
2
59
0
1
Order By: Relevance
“…27 We confirmed that the ACE genotype was not related to lung cancer 34 There is one study that investigated prostate cancer progression and observed more advanced tumors in DD carriers. 35 No significant relation was reported for ACE genotype and colorectal cancer risk.…”
Section: Discussionmentioning
confidence: 99%
“…27 We confirmed that the ACE genotype was not related to lung cancer 34 There is one study that investigated prostate cancer progression and observed more advanced tumors in DD carriers. 35 No significant relation was reported for ACE genotype and colorectal cancer risk.…”
Section: Discussionmentioning
confidence: 99%
“…144 The role of ACE in cancer is further supported by the findings that ACE polymorphism has been found to be associated with several cancers, including prostate, gastric and breast cancer. [145][146][147] Thus, several studies support anti-cancer effects of ACEis through RAS-dependent and/or -independent mechanisms, and these inhibitors may help us understand interactions between components of RAS in tumorigenesis and design new anti-cancer agents.…”
Section: Anticancer Effect Of Aceismentioning
confidence: 99%
“…[29][30][31][32][33][34][35][36] Furthermore, the genetic background may alter the natural history of prostate cancer development. [37][38][39] Moreover, impaired ability to undergo apoptosis seems to be important in prostate cancer. 40 Polymorphisms in the promoter region of the FAS and FASL genes alter the transcriptional activity of these genes, this could be an important role in Fas/FasL pathway.…”
Section: Introductionmentioning
confidence: 99%